Graphene quantum dots and their application in catalysis - Gong, Jun (Nanyang Technological University, 2021)
Graphene quantum dots (GQDs) are the latest addition to the nanocarbon family with outstanding photostability, tunable photoluminescence, good biocompatibility and physiochemical properties, demonstrating great potential for a wide variety of applications. But their practical use is hindered by the current high cost. In the first work, we demonstrate a scalable, low cost and high yield (~75%) bottom-up strategy using naphthalene as the precursor to synthesize undoped or heteroatom doped GQDs. Furthermore, Van der Waals heterojunctions (vdWHs) formed between 2D materials have attracted tremendous attention recently due to their extraordinary properties which cannot be offered by their individual components or other heterojunctions. Intriguing electronic coupling, lowered energy barrier, intimate charge transfer, efficient exciton separation occurring at the atomically sharp interface promise their applications in catalysis which, however, are largely unexplored and GQDs based vdWHs are barely reported. Herein, we demonstrate a 0D/2D vdWH between 0D GQDs and 2D pristine graphene sheets, simply prepared by ultrasonication of graphite powder using GQDs as intercalation surfactant. And such all-carbon Schottky-diode-like 0D/2D vdWHs are employed for the emerging photoelectrochemical catalysis (water splitting) with high performance. The demonstrated low-cost and scalable bottom-up growth of heteroatom-doped GQDs shall greatly promote their widespread applications. Moreover, the mechanisms underlying GQD growth and heterojunction mediated catalysis are revealed both experimentally and theoretically. Since the first mechanically exfoliated graphene in 2004, various atomically-thin 2D materials have emerged and changed the landscapes of many fields. Their applications however are hindered by lack of methods for scalable production with high quality. Herein, considering the structure similarities between graphene and other 2D nanomaterials, in the second work, a modified strategy is reported to exfoliate pristine single or few-layered 2D materials (MoS2, h-BN, WS2, g-C3N4 microsheets) using another bottom-up grown amphiphilic GQDs as both the intercalation agent and dispersant. Further, it is shown that the as-formed GQD/MoS2 vdWHs give enhanced performance for electrocatalysis of hydrogen evolution reaction owing to the synergistic coupling at the 0D/2D heterojunction. This study further unleashes the application potential of GQDs and GQD-based 0D/2D vdWHs. Furthermore, even various of GQD-based composites were reported but the role of GQD hasn’t been fully explored and understood. MoS2 is a promising catalyst to replace expensive Pt/C, however, suffering from poor HER performance in alkaline environment. For first time, we present a simple one-pot hydrothermal fabrication of GQD intercalated MoS2 with doping of single Co atoms (GQD/Co/MoS2). With the optimal amount of GQDs and an enlarged interlayer spacing of 9.7 Å, GQD/Co/MoS2 shows excellent HER activity in alkaline solution. Except for the heterojunction construction, GQDs displays a new role in engineering the structure of composites by increasing the interlayer spacing to enhance the performance of the composites. Moreover, this approach can be expanded to synthesize other transition metal doped MoS2 catalysts for elegant HER activity or other promising applications.